A DNA microarray for species identification of cetacean animals in Korean water - Park, Jung Youn; Kim, Ji-Hoon; An, Yong-Rock; Kim, Mi-Jung; Lee, Won Sun; An, Cheul Min; Jung, Jin-Wook; Kang, Jung-Ha; Moon, Hyo-Bang; Hwang, Seung Yong (Biochip journal, 2010)
Some whales caught incidentally or illegally in Korean waters have been introduced into the seafood market. Thus, the Korea Coast Guard (KCG) monitors and reports incidentally caught whales. However, species identification of some carcasses based on morphological features is difficult and often inaccurate, particular for processed whale products in the marketplace. For these reasons, we developed a DNA microarray that distinguishes 9 species of cetacean animals for quick and simple species identification. We verified genetic variations in whales and designed species-specific oligonucleotide probes by sequence analysis of mitochondrial cytochrome c oxidase subunit I. Fluorescent dye-labeled DNA targets were generated with a fluorescent dye-labeled primer and hybridized onto a DNA microarray consisting of short probes that were 29-37 nucleotides in length. A DNA microarray system using species-specific probes was successful at rapidly identifying 9 species of whales on the basis of hybridization patterns.